2013
DOI: 10.5603/fhc.2013.0032
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical study on survivin in sinonasal tumors and its relationship with the immunoexpression of Ki67 and Bcl-2

Abstract: Abstract:The immunoexpression of the inhibitor of apoptosis protein survivin has been shown to be a significant prognostic factor in various human cancers. Immunohistochemical method was used to examine the expression of survivin, Ki67 and Bcl-2 in 20 cases of sinonasal inverted papillomas (IPs), 12 cases of sinonasal squamous cell carcinoma (SNCs) and 19 cases of nasal chronic sinusitis as a control. Nuclear immunostaining for survivin was observed in 14 of 20 (70%) cases of sinonasal IPs and 10 of 12 (83.4%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…This hypothesis is consistent with the downregulation of Ki-67 in the current study, considering the previous evidence (Stasikowska-Kanicka, Wagrowska-Danilewicz, & Danilewicz, 2013;Tan et al, 2005).…”
Section: Discussionsupporting
confidence: 94%
“…This hypothesis is consistent with the downregulation of Ki-67 in the current study, considering the previous evidence (Stasikowska-Kanicka, Wagrowska-Danilewicz, & Danilewicz, 2013;Tan et al, 2005).…”
Section: Discussionsupporting
confidence: 94%
“…It is interesting to note that nuclear immunoexpression of Survivin was detected in some areas of the epithelium (Fig. 2f), which according to Stasikowska-Kanicka et al (32), fosters cell proliferation, while its cytoplasmic immunoexpression is involved in the mechanisms of apoptosis regulation. On the other hand, both Bcl-2 and Bax participate as transcriptional targets for p53, a tumor suppressor protein, which brings about cell cycle arrest or apoptosis in response to DNA damage.…”
Section: Discussionmentioning
confidence: 72%
“…Tsou et al [36] in a recent study on a cohort of 70 patients observed significantly elevated levels of Ki-67, p27, and PCNA in SNIPs with sinonasal SCC transformation compared with SNIPs without malignancy. Other authors have revealed that the nuclear immunoexpression of the inhibitor of apoptosis protein survivin and Bcl-2 oncoprotein immunoexpression are significantly higher in SNIP, suggesting that survivin and Bcl-2 may be involved in sinonasal tumorigenesis [37].…”
Section: Ki-67 Pcna Bcl-2mentioning
confidence: 99%